Representation of Latinas as Maids on Devious Maids (2013) - Sudirman, Fitria Afrianty (Paradigma: Jurnal Kajian Budaya, 2013)
This article aims to analyze the representation of Latinas as maids by examining the first season of US television drama comedy, Devious Maids. The show has been a controversy inside and outside Latina community since it presents the lives of five Latinas working as maids in Beverly Hills that appears to reinforce the negative stereotypes of Latinas. However, a close reading on scenes by using character analysis on two Latina characters shows that the characters break stereotypes in various ways. The show gives visibility to the Latinas by putting them as main characters and portraying them as progressive and independent women who also refuse the notion of white supremacy.